1988
DOI: 10.1007/bf01129176
|View full text |Cite
|
Sign up to set email alerts
|

Topographic distribution of the 40 Hz auditory evoked-Related potential in normal and aged subjects

Abstract: Galambos, Makeig and Talmachoff (1981) described what they called the 40 Hz event-related potential (ERP). This steady-state response is an EEG following response to repetitive auditory stimulation which becomes sinusoidal in form and maximal in amplitude at rates between 35 and 45 Hz. The present study was designed to examine the scalp topography of the 40 Hz ERP in order to complement previous magnetoencephalographic studies which implicate auditory cortex in the generation of the response. In addition, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 11 publications
1
22
1
1
Order By: Relevance
“…The topography of the EEG steady-state response in our study, with greatest amplitude in contralateral frontal electrodes, is a standard finding when the recording is performed with balanced earlobe reference electrodes (Azzena et al, 1995;Maiste et al, 1995). Using a noncephalic reference, the recordings show phase reversals in temporal regions (Johnson et al, 1988). This tangential dipole is better defined by magnetoencephalography (MEG) studies, which demonstrate the source in the primary auditory cortex, with a projection to central fields (Engelien et al, 2000).…”
Section: Neurophysiological Studymentioning
confidence: 60%
“…The topography of the EEG steady-state response in our study, with greatest amplitude in contralateral frontal electrodes, is a standard finding when the recording is performed with balanced earlobe reference electrodes (Azzena et al, 1995;Maiste et al, 1995). Using a noncephalic reference, the recordings show phase reversals in temporal regions (Johnson et al, 1988). This tangential dipole is better defined by magnetoencephalography (MEG) studies, which demonstrate the source in the primary auditory cortex, with a projection to central fields (Engelien et al, 2000).…”
Section: Neurophysiological Studymentioning
confidence: 60%
“…Comparison of 20-Hz and 40-Hz ASSRs detected by EEG found that most components of the 20-Hz ASSRs originated from the auditory cortices, whereas the 40-Hz ASSRs may contain components from lower brain locations than the cortex such as the medial geniculate body in addition to components originating from the auditory cortices [23], [29], [30]. However, when the ASSR is measured by MEG as in the present study, almost all of the recorded ASSRs were assumed to consist of cortical components for both 20-Hz and 40-Hs ASSRs [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 40-Hz oscillations have been observed in the cortex under certain conditions. For example, there are 40-Hz oscillations during physiological stimulation of the visual (Gray et al, 1989) or auditory cortex (Galambos et al, 1981; Spydell et al, 1985; MĂ€kelĂ€ and Hari, 1987; Johnson et al, 1988). In its absence, as occurs when P type calcium channels are (Ca 3.1) are deleted, there is a total lack of cognitive function.…”
Section: Cortical Neuronsmentioning
confidence: 99%